Anti-skin aging effect of (gracilaria birdiae) seaweeds extract / Nor Iwani Farzana Mohamad Zamri - Mohamad Zamri, Nor Iwani Farzana (2022)
Anti-aging research focuses mainly on slowing, preventing, or reversing the aging process mainly on the skin. Malaysians are exposed to hot temperatures, which might accelerate the aging process as one of the main factors that causes skin aging is ultra-violet (UV) radiation. Seaweed is one of the most useful and widely available natural skincare ingredients. It is a concentrated form of seawater that may absorb minerals from the surrounding water. Gracilaria birdiae contains a wide range of bioactive compounds that can potentiate many effects such as antibacterial, antifouling, and herbivore deterrents, as well as UV-screening agents. These bioactive compounds include carotenoids, terpenoids, xanthophylls, chlorophyll, vitamins, saturated and polyunsaturated fatty acids, amino acids, and antioxidants. In this study, we tested Gracilaria birdiae ethanolic extract for antioxidant activity using DPPH and anti-tyrosinase activity. Due to the central role of oxidant in skin aging, we hypothesized that G.birdiae extract to have significant anti-tyrosinase activity due to its antioxidant activity. G.birdiae extract showed substantial antioxidant activity where 0.15 mg/ml extract scavenged 27.88% DPPH. However, G.birdiae extract showed minimal or no inhibition on tyrosinase. Based on this finding, the hypothesis is rejected as G.birdiae extract exhibits only DPPH scavenging activity but cannot inhibit tyrosinase activity. Nonetheless, G.birdiae extract is still a good source of antioxidants and may be useful in various other oxidative disorders.